STRATEGIC READINESS OF PARTNERSHIP BETWEEN GOVERNMENT AND NON-PROFIT ORGANIZATIONS IN THE WASH IN HCF PROGRAM IN BANDARLAMPUNG CITY - Natalia, Angga; Aryani, Willia Novi; Yudha, Gesit (Jurnal Agregasi, 2025)
This article discusses the WASH Program in Healthcare Facilities initiated by one non-profit organization, the Way Seputih Conservation Foundation (YKWS), in collaboration with the Bandarlampung Health Department. This program is beneficial forpreventing the spread of diseases from water, sanitation, and hygiene facilities, while also serving as a campaign platform for clean and healthy living behaviors in the community. The lack of proper sanitation and sufficient clean water is the root cause of various health problems in society. The research methodology employs a qualitative approach using the strategic readinessmethod, which is part of the Public Policy Analysis study. The results indicate that the strategic readiness of the partnership between the Bandarlampung City Government and the Way Seputih Conservation Foundation (YKWS) demonstrates shared commitment, good coordination, sharing of experiences and expertise, and community participation. Additionally, challenges that need to be addressed include policy and funding issues, the need for monitoring and evaluation systems, sustainable management, and collaboration with relevant parties.